DEVELOPING STUDENT SPEAKING ACTIVITIES THROUGH VIDEO RECORDINGTECHNIC - Widiani Tresnaningsih (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2013)
Speaking skill is believed as an importantgoal of many English classes and courses. Thus, many ways,technics, researches are growing to find out better performance of the students.The use of technology nowadays is also developing fast in this case. Speaking activities are nor only done traditionally by having the students stand up in front of the class and recite the dialog.One of the alternatives is by using video recording technic. It is not something new in the English teaching learning, but some teachers are still not aware of it and have no clear ideas how to make use the video recording in their speaking subjects.This paper explores the benefits of using video recording technic in light of the kinds of activities to videotape in order to develop students’ speaking performances. The steps of speaking activities are going to be explained slightly as the view for those who are interested to apply in their speaking lessons..